Instrumento para sistematização da assistência de enfermagem para idosos com doenças infecciosas e parasitárias - Martins, Marineuma (2019)
Introduction: the elderly need special attention in health services and the nurse needs to be qualified to meet this population and their demands. Objectives: To analyze the evidence available in the literature on the use of nursing diagnoses and interventions for the elderly population with communicable and parasitic diseases. To identify nursing diagnoses and interventions used by nurses at the Parasitic Infectious Disease Clinic of the Lauro Wanderley University Hospital, Federal University of Paraíba, which are relevant to meeting the specific needs of the hospitalized elderly. To elaborate an instrument containing the nursing diagnoses and interventions, checklist type, for the elderly with infectious and parasitic diseases, hospitalized at the Parasitic Infectious Disease Clinic / Lauro Wanderley University Hospital, in order to subsidize the clinical practice of the nurse. Method: This is a methodological study developed in three stages: the first is an integrative review, the second covers the identification of nursing diagnoses and interventions considered or not relevant to the elderly by the clinic nurses and the third stage refers to the construction of the Nursing Diagnostic and Intervention Instrument for the elderly (product), to be used in the Nursing Care Systematization by nurses. Data were analyzed considering the Concordance Index of ≥ 0.9%. The study was approved in accordance with CAAE: 67103917.6.0000.5188 and Opinion No. 2,190,153. Results and discussions: from the four studies selected from the scientific literature on Nursing Diagnoses to the elderly with Communicable and Parasitic Diseases, it appears that most of the articles were published in 2015, in Brazil, and in Portuguese. . The results show the interest of the studies in the context of people living with the Human Immunodeficiency Virus and Acquired Immunodeficiency Syndrome, with emphasis on women, besides the identification and classification of terms, the construction of statements of nursing diagnoses. Thirteen nurses participated in the research, being two coordinators of the clinic and 11 assisting nurses, aged between 29 and 53 years, professional experience from 4 months to 16 years and all had already studied lato sensu graduate and three had strictu sensu graduate. Of the 59 Nursing Diagnoses and their 451 Nursing Interventions of the instrument used, 50 diagnoses reached the Concordance Index ≥ 0.9%, with nine diagnoses not relevant for the elderly. Of the 451 Nursing Interventions, 290 met the Concordance Index ≥ 0.9%, so 161 interventions were excluded by the nurses. With 50 Nursing Diagnoses and 290 Nursing Interventions considered relevant, a cut was established for the construction of the product using Nursing Diagnoses and Interventions with a Concordance Index of 1.0%, leaving 36 Diagnoses and 102 Nursing Interventions. Final considerations: The construction of an instrument to meet the specific demands of the elderly population hospitalized with infectious and parasitic diseases becomes important for the implementation of the nursing process, bringing improvements to improve nursing care.